Reincarnation of the myths: the evolution of fairy tales in modern literature - Shahrin, Tasnia (Brac University, 2023)
This thesis is submitted in partial fulfillment of the requirements for the degree of Masters of Arts in Teaching to Speakers of Other Languages, 2023.